한·칠레 FTA 농업부문 영향평가 - 최세균 (한국농촌경제연구원, 2006)
This research is designed to evaluate the impact of an FTA with Chile on the Korean agriculture since the FTA was in effect in 2004. In the evaluation, exchange rate, exporting price of Chilean products, are considered. The products interested in this research include grapes, wine, pork, and kiwi because the value of these four products amounts to $120 million in 2005, taking over 95% of total import from Chile. Chile's share in total Korea import has been increasing. The share of Chile in total agricultural import increased from 0.2% in 2001 to 0.6% in 2005. The share of Chile' meat rose from almost 0% in 2001 to 3.4% in 2005. It should be noted that all increases in import from Chile are not caused by the Korea-Chile FTA. Some increases in import were induced by the change in exporting price in Chile and the appreciation of the Korean won. For example, the import of Chilean grapes increased by $6.4 million between 2004 and 2005. Such increase in Chilean grapes import was affected by appreciation of Korean won, rise in exporting price in Chile, and shift in domestic demand as well as tariff reduction by the Korea-Chile FTA. Thus, it is of great importance to find net effect of the FTA from the gross increase in import of Chilean products. The impact of Chilean grapes import is about 3.7～7.5 billion won in 2005, 5.5～11.2 billon won in 2006 in terms of production value. It is not certain that Chilean grapes affected other fruits harvested in fall such as apples, pears, and mandarin oranges. In addition, the government subsidies for grape growers who decided to close farms contributed to maintaining domestic prices by 2.3% in 2005 and 3.4% in 2006. Domestic grape price would have fallen more if there had not been the subsidies. The Korea-Chile FTA is likely to have no impact on domestic kiwi producers because the import of Chilean kiwi is usually not overlapped with the production of domestic kiwi. Note that Chilean kiwi is imported between April and October while domestic kiwi is produced between November and May. For pork, it is not easy to analyze the Korea-Chile FTA because of lack of data, considering that Chilean pork began to be imported from 2002. Based on a cross elasticity of US pork, the impact of the FTA on the domestic pork industry was estimated indirectly. In value terms, the domestic production would have decreased by 2.7～8.0 billion won in 2004 and 5.4～16.0 billion won in 2005.